2015
DOI: 10.1111/cmi.12440
|View full text |Cite
|
Sign up to set email alerts
|

A touch of Zen: post-translational regulation of theLeishmaniastress response

Abstract: SummaryAcross bacterial, archaeal and eukaryotic kingdoms, heat shock proteins (HSPs) are defined as a class of highly conserved chaperone proteins that are rapidly induced in response to temperature increase through dedicated heat shock transcription factors. While this transcriptional response governs cellular adaptation of fungal, plant and animal cells to thermic shock and other forms of stress, early-branching eukaryotes of the kinetoplastid order, including trypanosomatid parasites, lack classical mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
0
19
0
1
Order By: Relevance
“…While chromosome copy number is mirrored by transcript levels in this study, these should be also reflected at the protein and metabolite levels to have a phenotypic effect. Although genes are constantly transcribed in a polycistronic manner by this process, it is likely that only a few specific genes required for adaptation to a given environment are the main drivers, with the expression levels of other genes regulated via posttranscriptional mechanisms (32). In our data set, we observed that although an overall correlation between the quantities of DNA and RNA exists, not all individual transcripts found on variable chromosomes change to the same extent: this was most obvious in the case of snoRNAs in chromosome 5 and one amastin array in chromosome 8.…”
Section: Discussionmentioning
confidence: 99%
“…While chromosome copy number is mirrored by transcript levels in this study, these should be also reflected at the protein and metabolite levels to have a phenotypic effect. Although genes are constantly transcribed in a polycistronic manner by this process, it is likely that only a few specific genes required for adaptation to a given environment are the main drivers, with the expression levels of other genes regulated via posttranscriptional mechanisms (32). In our data set, we observed that although an overall correlation between the quantities of DNA and RNA exists, not all individual transcripts found on variable chromosomes change to the same extent: this was most obvious in the case of snoRNAs in chromosome 5 and one amastin array in chromosome 8.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, protein stress may result from an event or treatment, which leads to protein failure when the protein is forced to sustain its duties under unnatural circumstances, such as environmental stress. Across seemingly all proteins, PTMs offer an extremely rapid solution for withstanding naturally occurring environmental stresses, such as microgravity [10], drought [11], thermic shock [12,13] and others. Stress responses resulting from the proteins themselves are also conducted by phosphorylation as in the case of initiation and regulation of tumor suppression by the p53 complex [6] and SUMOylation for its response to oxidative stress [7].…”
Section: Post-translational Modificationsmentioning
confidence: 99%
“…Macrophage‐internalized amastigotes are able to replicate and persist intracellularly, triggering long‐term latent infections that can lead to reactivation of disease years or decades after the primary infection. Both promastigotes and amastigotes of Leishmania are able to regulate the maturation of the parasitophorous vacuole in order to make it more hospitable and avoid destruction by the macrophage microbicidal activity and to overcome the host immune defense responses . For that purpose, macrophage defenses such as oxidative damage, antigen presentation, immune activation and apoptosis are compromised, and the parasite reprograms the macrophage to promote infection .…”
Section: Introductionmentioning
confidence: 99%
“…The phagosome achieves maturation by fusion with late endosomes and lysosomes resulting in the acquisition of lysosome‐associated molecules including LAMP‐1 and ‐2 , and cathepsins B, D, H and L . This phenomenon leads to a drop in pH and an elevation of temperature in the parasitophorous vacuole . It has been proposed that the acidic pH and high temperature participate in the developmental transition of the promastigote to the amastigote form, with the involvement of other signals including stress signals being probable .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation